Cannabidiol improves survival and behavioural co‐morbidities of Dravet syndrome in mice. (22nd April 2020) - Patra, Pabitra Hriday; Serafeimidou‐Pouliou, Eleni; Bazelot, Michael; Whalley, Benjamin Jason; Williams, Claire Michelle; McNeish, Alister James
Abstract : Background and Purpose: Dravet syndrome is a severe, genetic form of paediatric epilepsy associated with premature mortality and co‐morbidities such as anxiety, depression, autism, motor dysfunction and memory deficits. Cannabidiol is an approved anticonvulsive drug in the United States and Europe for seizures associated with Dravet syndrome in patients 2 years of age and older. We investigated its potential to prevent premature mortality and improve associated co‐morbidities. Experimental Approach: The efficacy of sub‐chronic cannabidiol administration in two mouse models of Dravet syndrome was investigated. The effect of cannabidiol on neonatal welfare and survival was studied using Scn1a −/− mice. We then used a hybrid, heterozygote Scn1a +/− mouse model to study the effect of cannabidiol on survival and behavioural co‐morbidities: motor deficits (rotarod and static‐beam test), gait abnormality (gait test), social anxiety (social interaction test), anxiety‐like (elevated plus maze) and depressive‐like behaviours (sucrose preference test) and cognitive impairment (radial arm maze test). Key Results: In Scn1a −/− mice, cannabidiol increased survival and delayed worsening of neonatal welfare. In Scn1a +/− mice, chronic cannabidiol administration did not show any adverse effect on motor function and gait, reduced premature mortality, improved social behaviour and memory function, and reduced anxiety‐like and depressive‐like behaviours. Conclusion and Implications: We are the first to demonstrate a potential disease‐modifying effect of cannabidiol in animal models of Dravet syndrome. Cannabidiol treatment reduced premature mortality and improved several behavioural co‐morbidities in Dravet syndrome mice. These crucial findings may be translated into human therapy to address behavioural co‐morbidities associated with Dravet syndrome.